Identification and Expression Profile Analysis of Chemosensory Genes From the Antennal Transcriptome of Bamboo Locust (Ceracris kiangsu) - Li, Ran; Jiang, Guo-Fang; Shu, Xiao-Han; Wang, Yu-Qi; Li, Ming-Jie (Frontiers in Physiology, 2020)
Studies of chemosensory genes are key to a better understanding of intra- and interspecific communications between insects and their environment and provide opportunities for developing environmentally friendly pesticides to target pest species. The bamboo locust Ceracris kiangsu Tsai (Orthoptera: Acrididae) is one of the most important bamboo leaf-eating insects in southern China. However, the genes underlying olfactory sensation are lacking in the bamboo locust. In this study, the transcriptomes of male and female C. kiangsu antennae were sequenced and analyzed. A total of 125 chemosensory genes, including 91 odorant receptors (ORs), 13 ionotropic receptors (IRs), 13 odorant-binding proteins (OBPs), six chemosensory proteins (CSPs), and two sensory neuron membrane proteins (SNMPs), were identified based on sequence alignment and phylogenetic analyses. The expression patterns of all candidate genes on the antennae of males and females, maxillary palps, tarsi, wings, and thoraxes-abdomens were confirmed by real-time quantitative PCR (qRT-PCR). The analyses demonstrated that most genes are highly expressed in the antennae, and 35 ORs, 7 IRs, 10 OBPs, and 1 CSP exhibit significantly male-biased expression patterns, indicating their potential functions in mating behavior and the recognition of female sex pheromones. In addition to the antennal-predominant genes, some were abundant in the maxillary palps and some in the non-olfactory tissues, suggesting their different functions in the olfactory system of C. kiangsu. Our research offers an extensive resource for investigating the chemoreception mechanism of C. kiangsu. Further studies of olfactory function will provide comprehensive methods and original strategies for integrated pest management (IPM).